Pulmonary arteriovenous malformations presenting as refractory heart failure - Liao, Ying (Pioneer Bioscience Publishing Company, 2014)
A 22-year-old young man with a history of idiopathic dilated cardiomyopathy (IDC) was admitted to our hospital due to difficult-to-control heart failure. A thoracic X-ray showed multiple nodules at the both pulmonary hilus and upper lobe of the right lung. Computed tomography (CT) angiography of the thorax confirmed arteriovenous malformation (AVM). However, effective treatment was impossible due to the poor physical condition; he died a few days later. Here we reported on the case of pulmonary arteriovenous malformations (PAVMs) being misdiagnosed as refractory heart failure.